Strategi Penegakan Hukum BNNP Maluku Utara dalam Menangani Kejahatan Narkotika: Peluang dan Hambatan - Mutalib, Dandi; Sari, Diah Ratu (Legalita, 2025)
This study examines the obstacles faced by investigators of the North Maluku Provincial National Narcotics Agency (BNNP) in handling narcotics crimes and analyzes the contributing factors that hinder effective law enforcement. Using a qualitative descriptive approach, the research collects data through interviews, documentation, and observation of BNNP officers and community members. The findings reveal that the primary challenges include the lack of adequate facilities and investigative technology, such as digital communication interception tools, and the increasing sophistication of narcotics distribution networks that utilize modern communication platforms. Additionally, the study identifies low public legal awareness and participation as major non-technical obstacles. Many community members are reluctant to report or cooperate with law enforcement due to fear of retaliation, indifference, or limited understanding of narcotics laws. These conditions significantly hinder BNNP’s ability to detect and prevent narcotics-related activities effectively. The analysis further indicates that overcoming these obstacles requires strengthening both technological infrastructure and community engagement. BNNP North Maluku is encouraged to enhance inter-agency coordination, improve investigative resources, and intensify public education programs on the dangers of narcotics. The study concludes that effective narcotics law enforcement demands a collaborative and integrative approach involving law enforcement institutions, government agencies, and active community participation to ensure sustainable prevention and eradication of narcotics crimes in North Maluku.